(untitled) (Advancements in Homeopathic Research, 2024)
Chronic low back pain is common problem worldwide. Low back pain is pain, muscle tension, or stiffness and chronic persists for twelve weeks. Chronic low back pain is common problem worldwide. Low back pain is pain, muscle tension, or stiffness and chronic persists for twelve weeks. Objectives To assess the effectiveness of “homoeopathic medicines with physiotherapy” as compared to “placebo with physiotherapy” for pain management in cases of chronic low back pain of Musculoskeletal Origin on the basis of the Pain Numeric Pain Rating Scale. To assess the effectiveness of “homoeopathic medicines with physiotherapy” as compared to “placebo with physiotherapy” for pain management in cases of chronic low back pain of Musculoskeletal Origin on the basis of Questionnaire (RMQ). To ascertain the predominant miasm in cases of chronic low back pain of Musculoskeletal Origin.